Access to European Union Agencies: Usual Suspects or Balanced Interest Representation in Open and Closed Consultations?. (29th December 2019) - Arras, Sarah; Beyers, Jan
Abstract: To facilitate stakeholder representation, European Union (EU) agencies use a range of procedures, including closed consultation or advisory committees and open or public consultations. For analysing what kind of stakeholders gain access to advisory committees, we compare these two particular procedures. Two theoretical perspectives guide this analysis. The first is a resource‐based account, which emphasizes informational needs and leads to the expectation that not only regulated interests but also EU‐level associations and European Commission expert group members will gain representation through closed consultations. The second is a norm‐based perspective that stresses the importance for agencies to establish a credible reputation, leading them to balance interest representation. A systematic comparison of stakeholders represented in agency committee with those participating in open consultations demonstrates that regulated interests have no systematic advantage in gaining access to closed consultations. Instead, closed consultations may diversify interest representation and facilitate the involvement of non‐business interests.